Environment-friendly phosphorus-free nitrogen-free scale and corrosion inhibition dispersant as well as preparation method and application thereof

By using environmentally friendly water treatment agents composed of itaconic acid-hydroxyethyl acrylate copolymer, the problem of eutrophication of water bodies and poor scale inhibition caused by existing water treatment agents is solved, and efficient scale inhibition is achieved , dispersing, corrosion inhibiting and biodegradable properties.

CN119409344AActive Publication Date: 2025-02-11ENERGY RESOURCES INST HEBEI ACADEMY OF SCI +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510011993.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-11
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

Most of the water treatment agents of existing industrial circulating cooling water contain phosphorus or nitrogen, which can easily cause eutrophication of water bodies for a long time. In addition, traditional synthetic polymer scale inhibitors have limited scale inhibition effects and are not biodegradable.

Method used

The environmentally friendly phosphorus-free nitrogen-free scale-resistant corrosion inhibiting dispersant consisting of itaconic acid-hydroxyethyl acrylate copolymer, polyepoxysuccinic acid, sodium gluconate and zinc sulfate heptahydrate, through synergistic increase between the components Effective mechanism to improve the scale-resistance, dispersion, corrosion-resistance and biodegradation properties of the agent.

Benefits of technology

It achieves excellent scale-resistance, dispersion, corrosion inhibition and biodegradation properties while using small amounts, avoids the problem of eutrophication of water bodies and reduces environmental load.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of water treatment, and provides an environment-friendly phosphorus-free nitrogen-free scale and corrosion inhibition dispersing agent as well as a preparation method and application of the environment-friendly phosphorus-free nitrogen-free scale and corrosion inhibition dispersing agent. The environment-friendly phosphorus-free nitrogen-free scale and corrosion inhibition dispersing agent is prepared from 18 to 22 parts of itaconic acid-hydroxyethyl acrylate copolymer, 20 to 30 parts of polyepoxysuccinic acid, 90 to 110 parts of sodium gluconate and 7 to 10 parts of zinc sulfate heptahydrate. The product provided by the invention has the advantages of small dosage, excellent scale inhibition, dispersion, corrosion inhibition, biodegradation and the like, excellent comprehensive performance, no phosphorus and no nitrogen, and avoids the problem of water eutrophication caused by long-term use of medicaments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment and relates to an environmentally friendly phosphorus-free and nitrogen-free scale and corrosion inhibitor dispersant and a preparation method and application thereof. Background Art

[0002] At present, most water treatment agents used for industrial circulating cooling water are phosphine-based formulas. However, because their components contain phosphorus or nitrogen or are non-biodegradable, long-term use can easily cause eutrophication of water bodies. It is a general trend for such agent formulas to be replaced by phosphorus-free, nitrogen-free and environmentally friendly agents.

[0003] While natural polymers are inexpensive and readily available, they are ineffective at inhibiting scale and contain high levels of impurities. Consequently, low-phosphorus, environmentally friendly synthetic polymer scale inhibitors have attracted widespread attention. For example, synthetic organic polymers such as polyacrylic acid and polymethacrylic acid, which are phosphorus-free scale inhibitors, have limited their treatment capacity due to their single functional group. Furthermore, these polymers are non-biodegradable, and long-term use can result in significant environmental impacts. Among them, the Chinese invention patent with publication number CN115536161A discloses an environmentally friendly phosphorus-free scale inhibitor and dispersant with excellent corrosion inhibition performance. The agent is composed of sodium itaconic acid-methyl propylene sulfonate, polyepoxysuccinic acid, sodium gluconate, and alkylolamide in a mass ratio of 32-47:10-20:98-102:8-12. However, the scale inhibitor and dispersant is used in large quantities and contains nitrogen, which is not environmentally friendly. The Chinese invention patent with publication number CN 117327232 A discloses a phosphorus-free, non-nitrogen-free green water treatment agent, its preparation method, and application. The agent is obtained by copolymerizing epoxysuccinic acid, itaconic acid, and hydroxyethyl acrylate. The molar ratio of epoxysuccinic acid, itaconic acid, and hydroxyethyl acrylate is 1.8-2.1:1.8-2.1:1. The biodegradability of the water treatment agent needs to be improved.

[0004] Therefore, it is of great significance to develop phosphorus-free and nitrogen-free green water treatment agents with excellent scale inhibition, dispersion, corrosion inhibition and biodegradation properties. Summary of the Invention

[0005] The present invention proposes an environmentally friendly phosphorus-free and nitrogen-free scale and corrosion inhibitor dispersant, as well as a preparation method and application thereof. While using a small amount, it has excellent scale inhibition, dispersing, corrosion inhibition and biodegradation properties, and has excellent comprehensive performance. At the same time, it is phosphorus-free and nitrogen-free, avoiding the eutrophication problem of water bodies caused by long-term use of the agent.

[0006] The technical solution of the present invention is achieved as follows: An environmentally friendly phosphorus-free and nitrogen-free scale and corrosion inhibitor dispersant is composed, by weight, of 18-22 parts of itaconic acid-hydroxyethyl acrylate copolymer, 20-30 parts of polyepoxysuccinic acid, 90-110 parts of sodium gluconate and 7-10 parts of zinc sulfate heptahydrate.

[0007] Preferably, the mixture is composed of 20 parts of itaconic acid-hydroxyethyl acrylate copolymer, 25 parts of polyepoxysuccinic acid, 100 parts of sodium gluconate and 8.83 parts of zinc sulfate heptahydrate, based on parts by mass.

[0008] Preferably, the average molecular weight of the polyepoxysuccinic acid is 900-1000.

[0009] Preferably, the average molecular weight of the polyepoxysuccinic acid is 950.

[0010] Preferably, the preparation method of the itaconic acid-hydroxyethyl acrylate copolymer comprises the following steps: Deionized water and tert-butyl alcohol are added to itaconic acid and hydroxyethyl acrylate in a molar ratio of 2.8-3.2:1. The temperature is raised to 60-70°C while nitrogen is introduced. Potassium persulfate solution and sodium sulfite solution are then added dropwise simultaneously until the addition is complete. The temperature is then raised to 80-90°C and the reaction is continued for 2.5-3.5 hours to obtain a light yellow, transparent IA-HEA polymerization solution. The itaconic acid-hydroxyethyl acrylate copolymer prepared by the present invention has a molecular weight of 15,000-20,000.

[0011] Preferably, the molar ratio of itaconic acid to hydroxyethyl acrylate is 3:1.

[0012] Preferably, the amount of deionized water added is 80-120% of the total mass of itaconic acid and hydroxyethyl acrylate.

[0013] Preferably, the amount of tert-butyl alcohol added is 12-18% of the total mass of itaconic acid and hydroxyethyl acrylate.

[0014] Preferably, the amount of potassium persulfate added is 5-10% of the total mass of itaconic acid and hydroxyethyl acrylate, and the molar ratio of sodium sulfite to potassium persulfate is 0.8-1.2:1.8-2.2.

[0015] Preferably, the mass concentration of the potassium persulfate solution and the sodium sulfite solution is 10%; the dropwise addition time of the potassium persulfate solution and the sodium sulfite solution is 0.5-1h.

[0016] The present invention also provides a method for preparing the environmentally friendly phosphorus-free and nitrogen-free scale and corrosion inhibitor dispersant as described above, comprising the following steps: mixing itaconic acid-hydroxyethyl acrylate copolymer, polyepoxysuccinic acid, sodium gluconate and zinc sulfate heptahydrate according to a proportion.

[0017] On the other hand, the environmentally friendly phosphorus-free and nitrogen-free scale and corrosion inhibitor dispersant described above can be used in the treatment of industrial circulating cooling water.

[0018] The working principle and beneficial effects of the present invention are: 1. In the present invention, polyepoxysuccinic acid, itaconic acid-hydroxyethyl acrylate copolymer, sodium gluconate and zinc sulfate heptahydrate interact with each other in a compatible synergistic mechanism. The synergistic effect of the components ensures the speed and density of film formation of the agent on the carbon steel surface, improves the scale inhibition, dispersion and corrosion inhibition effects of the agent, and at the same time, due to the synergistic effect of the components of the compound agent, the amount of agent used is reduced, the cost is reduced, and the environmental load is reduced; and the product is phosphorus- and nitrogen-free, avoiding the problem of eutrophication of water bodies caused by long-term use of the agent.

[0019] 2. Characteristics of the monomer components in the present invention: (1) Polyepoxysuccinic acid has excellent scale inhibition and corrosion inhibition performance, as well as good biocompatibility and biodegradability, and is a phosphorus-free and nitrogen-free, environmentally friendly agent; (2) Itaconic acid-hydroxyethyl acrylate copolymer is a phosphorus-free and nitrogen-free, biodegradable, environmentally friendly agent with excellent scale inhibition, dispersion and corrosion inhibition performance; (3) Sodium gluconate has good complexing ability for calcium, magnesium, iron and copper ions in water, and has an activation effect on many salts of these ions, so it has scale inhibition and corrosion inhibition effects, and has excellent biodegradability; (4) Zinc salt is a precipitation film type corrosion inhibitor, considering Zn 2+ Emission requirements, Zn in the formula 2+ The concentration is approximately 2 mg / L (i.e., the zinc sulfate heptahydrate concentration is approximately 8.83 mg / L). The synergistic effect between polyepoxysuccinic acid and itaconic acid-hydroxyethyl acrylate copolymer further enhances the scale inhibition and dispersion effectiveness of the agent, reducing under-scale corrosion in the water treatment system. Zinc sulfate heptahydrate, in conjunction with other components, further enhances the agent's corrosion inhibition performance.

[0020] 3. In the process of preparing itaconic acid-hydroxyethyl acrylate copolymer of the present invention, each reagent plays an irreplaceable role in the reaction. Tert-butyl alcohol acts as a chain transfer agent to adjust the molecular weight of the polymer. Sodium sulfite acts as a reducing agent. When used in combination with potassium persulfate, it initiates a free radical polymerization reaction. Its strong reducing ability is conducive to generating more active centers and increasing the reaction rate. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative work are within the scope of protection of the present invention. The materials used in the following examples and comparative examples can all be purchased commercially.

[0022] Example 1 A method for preparing an environmentally friendly phosphorus-free and nitrogen-free scale and corrosion inhibitor dispersant comprises the following steps: mixing, by mass, 20 parts of itaconic acid-hydroxyethyl acrylate copolymer, 25 parts of polyepoxysuccinic acid, 100 parts of sodium gluconate, and 8.83 parts of zinc sulfate heptahydrate; the average molecular weight of the polyepoxysuccinic acid is 950.

[0023] The preparation method of itaconic acid-hydroxyethyl acrylate copolymer comprises the following steps: In a four-necked flask equipped with a condenser and a thermometer, add itaconic acid (IA) and hydroxyethyl acrylate (HEA) at a molar ratio of 3:1, then add deionized water and tert-butyl alcohol. The amount of deionized water added is 100% of the total mass of itaconic acid and hydroxyethyl acrylate; the amount of tert-butyl alcohol added is 15% of the total mass of itaconic acid and hydroxyethyl acrylate. Place the four-necked flask in an oil bath with a stirring device, heat it to 65°C, introduce nitrogen, and turn off the condensation water; Use two syringe pumps to simultaneously add a potassium persulfate solution and a sodium sulfite solution with a mass concentration of 10%. The amount of potassium persulfate added is 7% of the total mass of itaconic acid and hydroxyethyl acrylate. The molar ratio of sodium sulfite to potassium persulfate is 1:2. The addition rate is set so that the two solutions are added simultaneously within 0.5 h. Then the temperature was continued to rise to 85° C., reacted for 3 h, cooled to room temperature and discharged to obtain a light yellow transparent IA-HEA polymerization solution, which was an itaconic acid-hydroxyethyl acrylate copolymer with an average molecular weight of 17710.

[0024] Example 2 A method for preparing an environmentally friendly phosphorus-free and nitrogen-free scale and corrosion inhibitor dispersant comprises the following steps: mixing, by mass, 18 parts of itaconic acid-hydroxyethyl acrylate copolymer, 30 parts of polyepoxysuccinic acid, 90 parts of sodium gluconate, and 10 parts of zinc sulfate heptahydrate; the average molecular weight of the polyepoxysuccinic acid is 950.

[0025] The preparation method of itaconic acid-hydroxyethyl acrylate copolymer comprises the following steps: In a four-necked flask equipped with a condenser and a thermometer, add itaconic acid (IA) and hydroxyethyl acrylate (HEA) at a molar ratio of 2.8:1, then add deionized water and tert-butyl alcohol. The amount of deionized water added is 120% of the total mass of itaconic acid and hydroxyethyl acrylate; the amount of tert-butyl alcohol added is 12% of the total mass of itaconic acid and hydroxyethyl acrylate. Place the four-necked flask in an oil bath with a stirring device, heat it to 70°C, introduce nitrogen, and turn off the condensation water; Use two syringe pumps to simultaneously add a 10% potassium persulfate solution and a sodium sulfite solution. The amount of potassium persulfate added is 5% of the total mass of itaconic acid and hydroxyethyl acrylate. The molar ratio of sodium sulfite to potassium persulfate is 1.2:1.8. Set the addition rate so that the two solutions are added simultaneously within 1 hour. The temperature was then continued to rise to 80° C., reacted for 3.5 hours, cooled to room temperature, and discharged to obtain a light yellow transparent IA-HEA polymerization solution, which was an itaconic acid-hydroxyethyl acrylate copolymer with an average molecular weight of 18100.

[0026] Example 3 A method for preparing an environmentally friendly phosphorus-free and nitrogen-free scale and corrosion inhibitor dispersant comprises the following steps: mixing, by mass, 22 parts of itaconic acid-hydroxyethyl acrylate copolymer, 20 parts of polyepoxysuccinic acid, 110 parts of sodium gluconate, and 7 parts of zinc sulfate heptahydrate; the average molecular weight of the polyepoxysuccinic acid is 950.

[0027] The preparation method of itaconic acid-hydroxyethyl acrylate copolymer comprises the following steps: In a four-necked flask equipped with a condenser and a thermometer, add itaconic acid (IA) and hydroxyethyl acrylate (HEA) at a molar ratio of 3.2:1, then add deionized water and tert-butyl alcohol. The amount of deionized water added is 80% of the total mass of itaconic acid and hydroxyethyl acrylate; the amount of tert-butyl alcohol added is 18% of the total mass of itaconic acid and hydroxyethyl acrylate. Place the four-necked flask in an oil bath with a stirring device, heat it to 60°C, introduce nitrogen, and turn off the condensation water; Use two syringe pumps to simultaneously add a 10% potassium persulfate solution and a 10% sodium sulfite solution. The amount of potassium persulfate added is 10% of the total mass of itaconic acid and hydroxyethyl acrylate. The molar ratio of sodium sulfite to potassium persulfate is 0.8:2.2. Set the addition rate so that both solutions are added simultaneously within 0.5 h. Then the temperature was continued to rise to 90° C., reacted for 2.5 hours, cooled to room temperature and discharged to obtain a light yellow transparent IA-HEA polymerization solution, which was an itaconic acid-hydroxyethyl acrylate copolymer with an average molecular weight of 16,800.

[0028] Comparative Example 1 A method for preparing a water treatment agent comprises the following steps: mixing, by mass, 25 parts of polyepoxysuccinic acid, 100 parts of sodium gluconate and 8.83 parts of zinc sulfate heptahydrate; the average molecular weight of the polyepoxysuccinic acid is 950.

[0029] Comparative Example 2 A method for preparing a water treatment agent comprises the following steps: mixing, by weight, 20 parts of itaconic acid-hydroxyethyl acrylate copolymer, 100 parts of sodium gluconate, and 8.83 parts of zinc sulfate heptahydrate; The preparation method of itaconic acid-hydroxyethyl acrylate copolymer comprises the following steps: In a four-necked flask equipped with a condenser and a thermometer, add itaconic acid (IA) and hydroxyethyl acrylate (HEA) at a molar ratio of 3:1, then add deionized water and tert-butyl alcohol. The amount of deionized water added is 100% of the total mass of itaconic acid and hydroxyethyl acrylate; the amount of tert-butyl alcohol added is 15% of the total mass of itaconic acid and hydroxyethyl acrylate. Place the four-necked flask in an oil bath with a stirring device, heat it to 65°C, introduce nitrogen, and turn off the condensation water; Use two syringe pumps to simultaneously add a potassium persulfate solution and a sodium sulfite solution with a mass concentration of 10%. The amount of potassium persulfate added is 7% of the total mass of itaconic acid and hydroxyethyl acrylate. The molar ratio of sodium sulfite to potassium persulfate is 1:2. The addition rate is set so that the two solutions are added simultaneously within 0.5 h. Then the temperature was continued to rise to 85° C., reacted for 3 h, cooled to room temperature and discharged to obtain a light yellow transparent IA-HEA polymerization solution, which was an itaconic acid-hydroxyethyl acrylate copolymer with an average molecular weight of 17710.

[0030] Comparative Example 3 A method for preparing a water treatment agent comprises the following steps: mixing, by mass, 100 parts of sodium gluconate and 8.83 parts of zinc sulfate heptahydrate.

[0031] Comparative Example 4 A preparation method of a water treatment agent comprises the following steps: mixing, by mass, 20 parts of itaconic acid-hydroxyethyl acrylate copolymer, 25 parts of polyepoxysuccinic acid and 100 parts of sodium gluconate; the average molecular weight of the polyepoxysuccinic acid is 950.

[0032] The preparation method of itaconic acid-hydroxyethyl acrylate copolymer comprises the following steps: In a four-necked flask equipped with a condenser and a thermometer, add itaconic acid (IA) and hydroxyethyl acrylate (HEA) at a molar ratio of 3:1, then add deionized water and tert-butyl alcohol. The amount of deionized water added is 100% of the total mass of itaconic acid and hydroxyethyl acrylate; the amount of tert-butyl alcohol added is 15% of the total mass of itaconic acid and hydroxyethyl acrylate. Place the four-necked flask in an oil bath with a stirring device, heat it to 65°C, introduce nitrogen, and turn off the condensation water; Use two syringe pumps to simultaneously add a potassium persulfate solution and a sodium sulfite solution with a mass concentration of 10%. The amount of potassium persulfate added is 7% of the total mass of itaconic acid and hydroxyethyl acrylate. The molar ratio of sodium sulfite to potassium persulfate is 1:2. The addition rate is set so that the two solutions are added simultaneously within 0.5 h. Then the temperature was continued to rise to 85° C., reacted for 3 h, cooled to room temperature and discharged to obtain a light yellow transparent IA-HEA polymerization solution, which was an itaconic acid-hydroxyethyl acrylate copolymer with an average molecular weight of 17710.

[0033] Comparative Example 5 A method for preparing a water treatment agent comprises the following steps: mixing, by mass, 20 parts of itaconic acid-hydroxyethyl acrylate copolymer, 25 parts of polyepoxysuccinic acid, 100 parts of sodium gluconate and 8.83 parts of zinc sulfate heptahydrate; the average molecular weight of the polyepoxysuccinic acid is 950.

[0034] The preparation method of itaconic acid-hydroxyethyl acrylate copolymer comprises the following steps: In a four-necked flask equipped with a condenser and a thermometer, add itaconic acid (IA) and hydroxyethyl acrylate (HEA) at a molar ratio of 2:1, then add deionized water and tert-butyl alcohol. The amount of deionized water added is 100% of the total mass of itaconic acid and hydroxyethyl acrylate; the amount of tert-butyl alcohol added is 15% of the total mass of itaconic acid and hydroxyethyl acrylate. Place the four-necked flask in an oil bath with a stirring device, heat it to 65°C, introduce nitrogen, and turn off the condensation water; Use two syringe pumps to simultaneously add a potassium persulfate solution and a sodium sulfite solution with a mass concentration of 10%. The amount of potassium persulfate added is 7% of the total mass of itaconic acid and hydroxyethyl acrylate. The molar ratio of sodium sulfite to potassium persulfate is 1:2. The addition rate is set so that the two solutions are added simultaneously within 0.5 h. Then the temperature was continued to rise to 85° C., reacted for 3 h, cooled to room temperature and then discharged to obtain a light yellow transparent IA-HEA polymerization solution, which is itaconic acid-hydroxyethyl acrylate copolymer.

[0035] Comparative Example 6 A method for preparing a water treatment agent comprises the following steps: mixing, by mass, 20 parts of itaconic acid-hydroxyethyl acrylate copolymer, 25 parts of polyepoxysuccinic acid, 100 parts of sodium gluconate and 8.83 parts of zinc sulfate heptahydrate; the average molecular weight of the polyepoxysuccinic acid is 950.

[0036] The preparation method of itaconic acid-hydroxyethyl acrylate copolymer comprises the following steps: In a four-necked flask equipped with a condenser and a thermometer, add itaconic acid (IA) and hydroxyethyl acrylate (HEA) at a molar ratio of 3:1, then add deionized water and isopropyl alcohol. The amount of deionized water added is 100% of the total mass of itaconic acid and hydroxyethyl acrylate; the amount of isopropyl alcohol added is 15% of the total mass of itaconic acid and hydroxyethyl acrylate. Place the four-necked flask in an oil bath with a stirring device, heat it to 65°C, introduce nitrogen, and turn off the condensation water; Use two syringe pumps to simultaneously add a potassium persulfate solution and a sodium sulfite solution with a mass concentration of 10%. The amount of potassium persulfate added is 7% of the total mass of itaconic acid and hydroxyethyl acrylate. The molar ratio of sodium sulfite to potassium persulfate is 1:2. The addition rate is set so that the two solutions are added simultaneously within 0.5 h. Then the temperature was continued to rise to 85° C., reacted for 3 h, cooled to room temperature and then discharged to obtain a light yellow transparent IA-HEA polymerization solution, which is itaconic acid-hydroxyethyl acrylate copolymer.

[0037] Comparative Example 7 A method for preparing a water treatment agent comprises the following steps: mixing, by mass, 20 parts of itaconic acid-hydroxyethyl acrylate copolymer, 25 parts of polyepoxysuccinic acid, 100 parts of sodium gluconate and 8.83 parts of zinc sulfate heptahydrate; the average molecular weight of the polyepoxysuccinic acid is 950.

[0038] The preparation method of itaconic acid-hydroxyethyl acrylate copolymer comprises the following steps: In a four-necked flask equipped with a condenser and a thermometer, add itaconic acid (IA) and hydroxyethyl acrylate (HEA) at a molar ratio of 3:1, then add deionized water and tert-butyl alcohol. The amount of deionized water added is 100% of the total mass of itaconic acid and hydroxyethyl acrylate; the amount of tert-butyl alcohol added is 15% of the total mass of itaconic acid and hydroxyethyl acrylate. Place the four-necked flask in an oil bath with a stirring device, heat it to 65°C, introduce nitrogen, and turn off the condensation water; Use two syringe pumps to simultaneously add ammonium persulfate solution and sodium sulfite solution with a mass concentration of 10%. The amount of potassium persulfate added is 7% of the total mass of itaconic acid and hydroxyethyl acrylate. The molar ratio of sodium sulfite to ammonium persulfate is 1:2. The addition rate is set so that the two solutions are added simultaneously within 0.5 hours. Then the temperature was continued to rise to 85° C., reacted for 3 h, cooled to room temperature and then discharged to obtain a light yellow transparent IA-HEA polymerization solution, which is itaconic acid-hydroxyethyl acrylate copolymer.

[0039] Comparative Example 8 A method for preparing a water treatment agent comprises the following steps: mixing, by mass, 20 parts of itaconic acid-hydroxyethyl acrylate copolymer, 25 parts of polyepoxysuccinic acid, 100 parts of sodium gluconate and 8.83 parts of zinc sulfate heptahydrate; the average molecular weight of the polyepoxysuccinic acid is 950.

[0040] The preparation method of itaconic acid-hydroxyethyl acrylate copolymer comprises the following steps: In a four-necked flask equipped with a condenser and a thermometer, add itaconic acid (IA) and hydroxyethyl acrylate (HEA) at a molar ratio of 3:1, then add deionized water and tert-butyl alcohol. The amount of deionized water added is 100% of the total mass of itaconic acid and hydroxyethyl acrylate; the amount of tert-butyl alcohol added is 15% of the total mass of itaconic acid and hydroxyethyl acrylate. Place the four-necked flask in an oil bath with a stirring device, heat it to 65°C, introduce nitrogen, and turn off the condensation water; Use two syringe pumps to simultaneously add a potassium persulfate solution and a sodium bisulfite solution with a mass concentration of 10%. The amount of potassium persulfate added is 7% of the total mass of itaconic acid and hydroxyethyl acrylate. The molar ratio of sodium bisulfite to potassium persulfate is 1:2. The addition rate is set so that the two solutions are added simultaneously within 0.5 h. Then the temperature was continued to rise to 85° C., reacted for 3 h, cooled to room temperature and then discharged to obtain a light yellow transparent IA-HEA polymerization solution, which is itaconic acid-hydroxyethyl acrylate copolymer.

[0041] Experimental effect example The performance and effects of the water treatment agents obtained in Examples 1-3 and Comparative Examples 1-8 were compared. The itaconic acid-hydroxyethyl acrylate copolymer prepared in Example 1 was used as Sample 1 (IA-HEA), polyepoxysuccinic acid was used as Sample 2 (PESA), and sodium gluconate was used as Sample 3 (PTT). The specific experimental methods are as follows: (1) Scale inhibition performance test ① Calcium phosphate blocking: According to the national standard GB / T22626-2008, distilled water was used to prepare Ca 2+ The mass concentration is 250 mg / L (calculated as CaCO3), PO4 3- Take 500 mL of test water with a mass concentration of 10 mg / L and pH = 9 (adjusted with borax) in a conical flask, add water treatment agent, and place in a constant temperature water bath at 80℃ for 10 hours. Take it out and cool it to room temperature. Take the supernatant and use a TU-1900 spectrophotometer (710 nm, 1 cm cuvette) to measure the PO4 content of the solution. 3- Calculate the scale inhibition rate or 2.

[0042]

[0043] in, C 0. C 1. C 2. PO4 in raw water after heating without adding chemicals, heating with adding chemicals and preparing at room temperature 3- Mass concentration, mg / L.

[0044] ② Calcium carbonate inhibition: According to the national standard GB / T16632-2008, distilled water was used to prepare Ca 2+ and HCO3 - The test water with mass concentration of 600 mg / L and 1200 mg / L (both in terms of CaCO3) was added with water treatment agent and heated in a constant temperature water bath at 80°C for 10 h. 2+ The scale inhibition rate is calculated based on the concentration of

[0045] (2) Dispersion performance test Add a certain amount of water treatment agent and ferrous sulfate to the water and stir vigorously to hydrolyze and oxidize the ferrous ions to simulate the iron oxide scale deposition process caused by metal corrosion and other reasons in the industrial circulating water system. The reaction is shown below.

[0046]

[0047] FeSO4 is hydrolyzed at a high pH value to generate Fe2O3 as a suspension medium system. After standing for a period of time, the iron oxide dispersion performance of the agent is judged by measuring the transmittance of the supernatant. The better the dispersion performance, the lower the transmittance.

[0048] (3) Corrosion inhibition performance evaluation The present invention refers to GB / T1875-2000 "Determination of corrosion inhibition performance of water treatment agents - Rotating coupon corrosion test method", the test conditions are: temperature 40 ° C, rotation speed 80 r / min, no pre-film coupon, time 72h, A3 carbon steel test piece, surface area 28cm 2 The test water was groundwater from a residential area in Shijiazhuang. The water quality analysis results are shown in Table 1.

[0049] Table 1 Water quality analysis results of test water

[0050] (4) Biodegradation performance evaluation A mixed solution of water treatment agent and microbial inoculum was incubated using a shaking incubator. The COD of the mixed solution was measured on day 28, and the degradation rate was calculated based on the COD change. The biodegradability evaluation criteria in Table 2 were used to evaluate the tested substances.

[0051] Table 2 Biodegradability evaluation criteria

[0052] COD measurement test method: Approximately 100 g of garden soil was placed in 1 L of distilled water. Stir thoroughly, allow to settle for 2 hours, and filter. Discard approximately 200 mL of the supernatant. The remaining solution is the solution containing the microbial inoculum. Add 0.5 mL of the inoculum to an Erlenmeyer flask containing a water treatment agent at a specific concentration. The flask was capped and placed in a shaker at a constant temperature (maintained at approximately 25°C). The COD of the sample was measured 28 days after the start of the experiment.

[0053] (5) Results: After measurement, the performance of the water treatment agents obtained from Examples 1-3, Comparative Examples 1-8 and Samples 1-3 are shown in Table 3: Table 3

[0054] In Table 3, the dosage of Example 1 is 20 mg / L IA-HEA + 25 mg / L PESA + 100 mg / L PTT + 8.83 mg / L zinc sulfate heptahydrate; Example 2: The dosage is 18 mg / L IA-HEA + 30 mg / L PESA + 90 mg / L PTT + 10 mg / L zinc sulfate heptahydrate; Example 3: The dosage is 22 mg / L IA-HEA + 20 mg / L PESA + 110 mg / L PTT + 7 mg / L zinc sulfate heptahydrate; Comparative Example 1: 25 mg / L PESA + 100 mg / L PTT + 8.83 mg / L zinc sulfate heptahydrate; Comparative Example 2: 20 mg / L IA-HEA + 100 mg / L PTT + 8.83 mg / L zinc sulfate heptahydrate; Comparative Example 3: 100 mg / L PTT + 8.83 mg / L zinc sulfate heptahydrate. Comparative Example 4: 20 mg / L IA-HEA + 25 mg / L PESA + 100 mg / L PTT; The dosages used in Comparative Examples 5-8 are the same as those in Example 1.

[0055] IA-HEA represents itaconic acid-hydroxyethyl acrylate copolymer, PESA represents polyepoxysuccinic acid, and PTT represents sodium gluconate.

[0056] Testing showed that the water treatment agent formulations obtained in Examples 1-3 exhibited superior scale inhibition, dispersibility, and corrosion inhibition properties compared to the comparative example, as well as good biodegradability and ideal overall performance. The itaconic acid-hydroxyethyl acrylate copolymers in the water treatment agent formulations obtained in Examples 1-3 had a dispersity index (PDI, measured by gel permeation chromatography (GPC)) of approximately 1. Comparative Examples 6-8 employed different chain transfer agents, initiators, and redox systems in their preparation methods, resulting in polymers with lower average molecular weights and higher dispersities than the itaconic acid-hydroxyethyl acrylate copolymers in Examples 1-3. Their scale inhibition, dispersibility, and corrosion inhibition properties were affected to varying degrees. This was attributed to the different half-lives of ammonium persulfate and potassium persulfate as initiators, which resulted in different polymerization reaction rates. The chain transfer agent, tert-butyl alcohol, also modulated the molecular weight. Furthermore, sodium sulfite and potassium persulfate acted as redox systems during the polymerization reaction, affecting the reaction rate and, ultimately, the molecular weight of the polymer, thereby impacting its scale inhibition, dispersibility, and corrosion inhibition properties.

[0057] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An environmentally friendly phosphorus-free and nitrogen-free scale and corrosion inhibitor dispersant, characterized in that: The invention comprises, by weight, 18-22 parts of itaconic acid-hydroxyethyl acrylate copolymer, 20-30 parts of polyepoxysuccinic acid, 90-110 parts of sodium gluconate and 7-10 parts of zinc sulfate heptahydrate.

2. The environmentally friendly phosphorus-free and nitrogen-free scale and corrosion inhibitor dispersant according to claim 1, characterized in that: The composition is composed of 20 parts of itaconic acid-hydroxyethyl acrylate copolymer, 25 parts of polyepoxysuccinic acid, 100 parts of sodium gluconate and 8.83 parts of zinc sulfate heptahydrate, in parts by mass.

3. The environmentally friendly phosphorus-free and nitrogen-free scale and corrosion inhibitor dispersant according to claim 1, characterized in that: The average molecular weight of the polyepoxysuccinic acid is 900-1000.

4. The environmentally friendly phosphorus-free and nitrogen-free scale and corrosion inhibitor dispersant according to claim 1, characterized in that: The preparation method of the itaconic acid-hydroxyethyl acrylate copolymer comprises the following steps: Deionized water and tert-butanol are added to itaconic acid and hydroxyethyl acrylate in a molar ratio of 2.8-3.2:1, and the temperature is raised to 60-70°C while nitrogen is introduced; then potassium persulfate solution and sodium sulfite solution are added dropwise at the same time, and the addition is completed at the same time, and then the temperature is continued to be raised to 80-90°C, and the reaction is carried out for 2.5-3.5 hours to obtain a light yellow transparent IA-HEA polymerization solution.

5. The environmentally friendly phosphorus-free and nitrogen-free scale and corrosion inhibitor dispersant according to claim 4, characterized in that: The amount of deionized water added is 80-120% of the total mass of itaconic acid and hydroxyethyl acrylate.

6. The environmentally friendly phosphorus-free and nitrogen-free scale and corrosion inhibitor dispersant according to claim 4, characterized in that: The amount of tert-butyl alcohol added is 12-18% of the total mass of itaconic acid and hydroxyethyl acrylate.

7. The environmentally friendly phosphorus-free and nitrogen-free scale and corrosion inhibitor dispersant according to claim 4, characterized in that: The amount of potassium persulfate added is 5-10% of the total mass of itaconic acid and hydroxyethyl acrylate, and the molar ratio of sodium sulfite to potassium persulfate is 0.8-1.2:1.8-2.

2.

8. The environmentally friendly phosphorus-free and nitrogen-free scale and corrosion inhibitor dispersant according to claim 4, characterized in that: The mass concentration of the potassium persulfate solution and the sodium sulfite solution is 10%; the dropping time of the potassium persulfate solution and the sodium sulfite solution is 0.5-1h.

9. A method for preparing an environmentally friendly phosphorus-free and nitrogen-free scale and corrosion inhibitor dispersant as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: Itaconic acid-hydroxyethyl acrylate copolymer, polyepoxysuccinic acid, sodium gluconate and zinc sulfate heptahydrate are mixed according to a proportion.

10. Use of the environmentally friendly phosphorus-free and nitrogen-free scale and corrosion inhibitor dispersant according to any one of claims 1 to 8 in the treatment of industrial circulating cooling water.

Citation Information

Patent Citations

  • Environment-friendly phosphorus-free scale inhibition dispersant with excellent corrosion inhibition performance

    CN115536161A

  • No-phosphate corrosion and scale inhibitor and its application

    CN101066811A

  • Preparation method and applications of phosphorus-free scale-inhibiting and corrosion-inhibiting agent for reusing reclaimed water in power plant

    CN106242096A

  • Phosphorus-free and nitrogen-free green water treatment agent as well as preparation method and application thereof

    CN117327232A

  • Corrosion inhibiting compositions

    US20030065116A1